Model-based channel estimator for correlated fading channels and channel estimation method thereof - Chen Yen-Chih; Cheng Chien-Chun; Su Yu-Ted (My University, 2013)
A model-based channel estimator for correlated fading channels adapted to a multiple-input multiple-output (MIMO) system, estimates a coefficient vector of a channel matrix for a given angle of departure (AoD) according to a plurality of received signals, a plurality of transmit pilots, a plurality of known model orders, and a plurality of predetermined bases for exploiting time, frequency, spatial channel correlation among a transmit antenna array, and spatial channel correlation among a receive antenna array, then estimates a mean AoD based on the estimated channel matrix. The channel estimator estimates iteratively the coefficient vector and the mean AoD until a stop criterion is met. Then, it reconstructs a channel estimate by using the plurality of predetermined bases, the coefficient vector, and the mean AoD.